2020
DOI: 10.1111/jfb.14611
|View full text |Cite
|
Sign up to set email alerts
|

Advances in understanding the impacts of global warming on marine fishes farmed offshore: Sparus aurata as a case study

Abstract: Monitoring variations in proteins involved in metabolic processes, oxidative stress responses, cell signalling and protein homeostasis is a powerful tool for developing hypotheses of how environmental variations affect marine organisms' physiology and biology. According to the oxygen-and capacity-limited thermal tolerance hypothesis, thermal acclimation mechanisms such as adjusting the activities of enzymes of intermediary metabolism and of antioxidant defence mechanisms, inducing heat shock proteins (Hsps) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 172 publications
(324 reference statements)
0
17
0
Order By: Relevance
“…Alfonso et al (2021) appraise information about effects of warming on stress physiology in fishes, based on laboratory studies, and how this may provide insight into what can be expected in wild populations. They consider how chronic temperature increase constitutes a physiological load that can alter the ability of fishes to cope with additional stressors, while extreme heatwaves would engender direct stress responses, all with potential consequences for fitness Feidantsis et al (2021). propose that studying the impacts of climactic temperature variation, on fishes farmed in offshore cages, can provide valuable understanding of physiological responses in natural populations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Alfonso et al (2021) appraise information about effects of warming on stress physiology in fishes, based on laboratory studies, and how this may provide insight into what can be expected in wild populations. They consider how chronic temperature increase constitutes a physiological load that can alter the ability of fishes to cope with additional stressors, while extreme heatwaves would engender direct stress responses, all with potential consequences for fitness Feidantsis et al (2021). propose that studying the impacts of climactic temperature variation, on fishes farmed in offshore cages, can provide valuable understanding of physiological responses in natural populations.…”
mentioning
confidence: 99%
“…Feidantsis et al . (2021) propose that studying the impacts of climactic temperature variation, on fishes farmed in offshore cages, can provide valuable understanding of physiological responses in natural populations. Taking the gilthead seabream Sparus aurata L. 1758 in the Mediterranean Sea as a case study, they review impacts of natural thermal regimes on a diversity of biochemical and molecular markers of performance and stress, plus behaviours such as responsiveness and appetite.…”
mentioning
confidence: 99%
“…While LDH and AST levels were higher at 17 • C, ALP was very high in animals kept at 23 • C. Then, after the temperature switch, ALP, AST, and LDH were found to be influenced by dietary lipids, with greater levels in response to high dietary lipid diet (L21). In the present study, the elevated blood LDH activity found at low temperatures before temperature changes could probably be caused by lactate accumulation in aerobic tissues such as red muscle and heart indicating an activation of the anaerobic component of metabolism during exposure to cold (Faggio et al, 2014;Feidantsis et al, 2020b). Before temperature switch, TRIG and HDL were more elevated at 17 • C. These results are consistent with increased triglyceride levels found during the colder months, interpreted as a mobilization of the lipid deposits to use as fuels by Faggio et al (2014).…”
Section: Discussionmentioning
confidence: 47%
“…This was another reason that this study only considered if there was a link between climate stressors and impacts and did not assign risk scores. The use of studies in predicting the behavioural and physiological responses to extremes in the wild or farm environment is limited, as the range of responses available to fish and complex interactions of competing environmental influences cannot be fully replicated in the laboratory and there must be caution on interpretation of results from experimental and tank trials [274][275][276].There is a need for more research that integrates farm-level monitoring data and fieldwork with the results of controlled tank trials and laboratory experiments, to better inform predictive computer modelling and impact assessments.…”
Section: Plos Climatementioning
confidence: 99%